Inhibition of Caspase-2 Activity in Human Jurkat T-cell Lymphoma Cells by Splice Switching Oligonucleotide to its pre-mRNA - Zhdanov, D.D.; Plyasova, A.A.; Gladilina, Yu.A.; Pokrovskaya, M.V.; Alexandrova, S.S.; Sokolov, N.N. (Biomedical Chemistry: Research and Methods, 2019)
Caspase-2 is a key enzyme thinvolved in induction of apoptosis. The caspase-2 level is regulated by alternative splicing (AS) of its mRNA. The aim of this work was to determine the ability of an oligonucleotide complementary to Casp-2 pre-mRNA to induce AS. This oligonucleotide blocked the binding of splicing-regulating proteins to their sites at the end of exon 9 of Casp-2 pre-mRNA, leading to induction of AS of Casp-2 mRNA. The decrease in expression of full-size active splice-variant (Casp-2L) and the increase the expression of a shortened variant (Casp-2S) was demonstrated in human T-cell lymphoma Jurkat cell line. The expression level of total Casp-2 remained unchanged. Disproportion of splice variants of Casp-2 led to inhibition of enzymatic activity of caspase-2.